Corrigendum: Tribological characteristics of natural fiber composite - Review (IOP Conf. Ser.: Mater. Sci. Eng 954 (2020) 012048). Issue 1 (October 2020) - Mohan, K.; Rajmohan, T.
Abstract : Page 1: The figure 1 should be updated. In the Introduction section, the following text appears in below the graph: "Figure 1 Number of articles published based on tribological evaluation of synthetic and natural fibers [4]." This should read: "Figure 1 - Number of articles published based on tribological evaluation of natural fibers [4]."